KEPENTINGAN CINA MENJALIN KERJASAMA FDI (FOREIGN DIRECT INVESTMENT) DALAM BIDANG ENERGI (MINYAK DAN GAS) DENGAN INDONESIA - Naomi Citra Srikandi; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Energy is one of the important main sources for the industrialization of country. However, some countries has limited natural resources. China that has energy security cooperates with Indonesia that has more energy and natural resources. Finally, The name of cooperation is Indonesia-China Energy Forum (ICEF). In 2002, there’s 3 (tree) of china’s company that operation in Indonesia, that’s CNPC, CNOOC, and SINOPEC.This research describes about the interest of China in FDI coorporation about oil and gas with Indonesia. China cooporates in FDI with Indonesia want to fulfill energy needs and has economic’s interest.Keyword: Energy security, economic’s interest, ICEF, oil and gas.